2016
DOI: 10.1038/srep39082
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based activity prediction of CYP21A2 stability variants: A survey of available gene variations

Abstract: Congenital adrenal hyperplasia due to 21-hydroxylase deficiency accounts for 90–95% of CAH cases. In this work we performed an extensive survey of mutations and SNPs modifying the coding sequence of the CYP21A2 gene. Using bioinformatic tools and two plausible CYP21A2 structures as templates, we initially classified all known mutants (n = 343) according to their putative functional impacts, which were either reported in the literature or inferred from structural models. We then performed a detailed analysis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…The fact is that the mutations were all in homozygous condition and never been reported previously. The R369Q mutation consists of arginine/glutamine substitution in position 1106 (c.1106G > A), 11 probably, this mutation is less relevant than other mutations for the phenotype of the present case, since it is generally associated with nonclassical CAH. 12 The other two mutations are referred to as "gene conversion mutations," although the underlying mechanism has not been fully clarified.…”
Section: Discussionmentioning
confidence: 81%
“…The fact is that the mutations were all in homozygous condition and never been reported previously. The R369Q mutation consists of arginine/glutamine substitution in position 1106 (c.1106G > A), 11 probably, this mutation is less relevant than other mutations for the phenotype of the present case, since it is generally associated with nonclassical CAH. 12 The other two mutations are referred to as "gene conversion mutations," although the underlying mechanism has not been fully clarified.…”
Section: Discussionmentioning
confidence: 81%
“…We found 35 rare or novel variants among the 343 sequenced samples (60 nonrelated alleles: 24 (14.5%) alleles from classical patients and 36 (7.2%) from NC, Table S1). We had previously reported 12 of these rare genetic variants 20,21,23,27 . In this study, we found three additional novel variants: p.(S166F) (GenBank ID: MH310941), p.(P189R) (GenBank ID: MH310942) and p.(R436L) (GenBank ID: MH310943) (see Table S2 for a summary of the clinical description of the patients).…”
Section: Resultsmentioning
confidence: 99%
“…CYP21A2 p.(S166F), p.(P189R), p.(G264R) and p.(R436L) variants were classified and evaluated as previously described 27 using PDB ID: 4Y8W 28 with progesterone and PDB ID: 5VBU with 17‐hydroxyprogesterone 29 as the human 21‐hydroxylase templates. UCSF Chimera program was used for structural visualization 30 and Adobe Photoshop CC 2019 program (http://www.adobe.com) for the compilation of the images.…”
Section: Methodsmentioning
confidence: 99%
“…8 Yet, despite the large number of reported mutations, approximately 10 mutations account for the majority of affected alleles. Most mutations result from gene conversion events.…”
Section: Molecular Geneticsmentioning
confidence: 99%